Effects of Forwarder Operation on Soil Physical Characteristics: a Case Study in the Italian Alps - Stefano Grigolato; Francesco Neri; Rodolfo Picchio; Enrico Marchi; Martina Cambi (Croatian Journal of Forest Engineering, 2016)
One of the most important issues in ground based wood extraction in forestry is to minimize the soil damage caused by heavy forestry machines. Generally, harvesting effects include changes in vegetation nutrient availability, soil microclimate/structure and litter quantity/ quality. Several studies were carried out on the impacts of heavy machines on the soil. However, only few studies took into consideration the effect of bogie tracks on the soil. The research focuses on the influence of forwarder machines equipped with bogie tracks on the soil compaction through changes of physical soil parameters and precisely bulk density, porosity, shear and penetration resistance. The study was carried out in a conifer stand of Larix decidua Mill. and Picea abies L. in a forest of North-eastern Italy during logging with forwarder. In this site, 3 tracks were identified, 2 concerned loaded forwarder passages and 1 control (no passages). The tracks were: (i) track A with a slope of 31% with 2 passages and track B with a slope of 3% having 10 passages. Soil samples were collected on all tracks in order to determine the influence of forwarder passes on soil physical properties. The results showed a different impact of logging operations on the soil of different tracks.